2015
DOI: 10.1002/term.1985
|View full text |Cite
|
Sign up to set email alerts
|

Micropattern size‐dependent endothelial differentiation from a human induced pluripotent stem cell line

Abstract: The multifaceted extracellular milieu presents biochemical and biophysical stimuli that influence stem cell differentiation. Two-dimensional (2D) micropatterned substrates allow the presentation of these cues in spatially defined geometries that have been demonstrated to guide stem cell fate decisions. Leveraging stem cells to reconstruct microvasculature, made up of an inner lining of endothelial cells (ECs) supported by pericytes, is critical to tissue-engineering advances; thus, methods to improve endotheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…We have previously shown that micropatterning influences autocrine and paracrine signalling during PSC maintenance and differentiation111314, and speculate that endogenous control over signalling pathways plays an important role in the haematopoietic differentiation system described here as well. Consistent with our data set, smaller islands of micropatterned hPSCs have been reported to be efficient in endothelial differentiation compared to larger islands45—perhaps due to lower levels of inhibitory factors. We observed that IP-10 endogenously inhibited hPSC-derived haematopoietic induction in non-micropatterned conditions, and its concentration can be attenuated by configuring HE cells into smaller colonies, rescuing haematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…We have previously shown that micropatterning influences autocrine and paracrine signalling during PSC maintenance and differentiation111314, and speculate that endogenous control over signalling pathways plays an important role in the haematopoietic differentiation system described here as well. Consistent with our data set, smaller islands of micropatterned hPSCs have been reported to be efficient in endothelial differentiation compared to larger islands45—perhaps due to lower levels of inhibitory factors. We observed that IP-10 endogenously inhibited hPSC-derived haematopoietic induction in non-micropatterned conditions, and its concentration can be attenuated by configuring HE cells into smaller colonies, rescuing haematopoietic differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…It has been shown that constrain endothelial cells in a geometrical cue has an impact on their fate (Huang et al, , ; Schaffer, ). With their work, Kusuma, Smith, Facklam, and Gerecht () showed that on 2D micropatterned surfaces (grafted with fibronectin), human induced pluripotent stem cells cultured on smaller islands of fibronectin promoted endothelial cells (ECs) differentiation with a yield of 70% for 80 μm of diameter against 50% for cells seeded onto bigger patterns 225 and 500 μm. Here once again, the size of the 2D structuration matters and allows a better regulation of differentiation of cells.…”
Section: Discussionmentioning
confidence: 99%
“…We find that the combination of these approaches unveils the importance of cell density and cytoskeletal tension in how hiPSCs sense their environment and differentiate to the mesodermal lineage toward vascular fates. mesodermal populations are sensitive to spatial confinement during vascular specification (15). Micropatterning tools have further uncovered the role of the cytoskeleton during differentiation through analysis of how RhoA/Rho-associated kinase (ROCK) impacts actomyosin contractility in MSCs undergoing fate decision toward adipocyte and osteocyte lineages (16)(17)(18)(19).…”
mentioning
confidence: 99%